Analyses of Copy Number Variations in Myxopapillary Ependymomas of Cauda Equina - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2019)
AIM: To identify the copy number variations that are specific to myxopapillary ependymomas (MPEs) of the cauda equina. MATERIAL and METHODS: The patient cohort included five patients who underwent resection of histologically confirmed MPEs. Tumor samples collected during surgery and stored in liquid nitrogen as well as corresponding blood samples collected were analyzed. Genomic DNA from the venous blood and tumor samples was obtained using standard techniques and hybridized to a Cytoscan 750K Array in accordance with the manufacturer's introductions. RESULTS: As a novel finding, amplification on chromosome 14q32.33 was detected in all tumor and blood samples, except one tumor sample. All tumor tissues also showed amplification on chromosomes 5, 7, 9, and 16. CONCLUSION: Although further studies with larger cohorts are required to identify genes involved in MPE tumorigenesis and to validate our results, these findings provide a basis for advanced molecular biological and genetic studies of MPEs.
Keywords: Myxopapillary ependymoma; Copy number variation; Cauda equina; Molecular biology; Chromosomal aberration; C11ORF95-RELA FUSIONS; TUMORS; CLASSIFICATION; COMPARTMENTS